Extracción e identificación de metabolitos secundarios y actividad antimicrobiana en Chromolaena bullata (Klatt) King & Robinson - García Sánchez, Luís Carlos; Corredor Barinas, John Alexander; Guerrero, José; Navas, Alejandro (Revista Científica, 2007)
The activity against the microorganisms Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosaand Candida albicans of the total extracts and the petroleum ether, dichloromethane and ethanol from the aerial parts of the vegetal species Chromolaena bullata (Klatt) King and Robinson was evaluated; two secondary metabolites were isolated and purified from leaves of this species, whose structures were elucidated through their physical and chemical properties and by spectroscopic techniques (uv, Gc-MS y RMN).